(untitled) (Medico Legal Update, 2020)
This study was performed within the DM center in Al-Sadder Teaching Hospital in Al-Najaf province to see the impact of not having breakfast for males in relation with Diabetes Mellitus sort two and supermolecule Profile. This study includes (25) male that not having breakfast , and (5) male that thought to be management cluster. (The results show important increase (P?0.05) in abstinence glucose, cholesterin, acylglycerol, LDL, lipoprotein and high-density lipoprotein in comparison with management group).